Digital Transformation and Islamic Value Integration in Islamic Religious Education: A Case Study at SMAN 1 Pangkalpinang - Feni Yulianti; Shinta Lestari Oktarini (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
Abstract This study examines the transformation of Islamic Religious Education in the digital age at SMAN 1 Pangkalpinang, focusing on teacher readiness, adaptive teaching strategies, and the role of digital learning in shaping students’ character. A qualitative case study approach within an interpretive paradigm was employed. Participants included four Islamic Religious Education teachers, one principal, one vice principal for curriculum affairs, and eight students selected through purposive sampling. Data were collected through semi-structured interviews, non-participant classroom observations, and document analysis. Data analysis followed the Miles and Huberman interactive model, supported by thematic coding. Trustworthiness was established through source triangulation, member checking, peer debriefing, and audit trails. The findings indicate that Islamic Religious Education teachers demonstrate adaptive-transformative readiness characterized by pedagogical resilience, creativity in utilizing limited digital resources, and the integration of Islamic values into digital learning. Teachers implemented adaptive strategies through blended learning, digital content curation, religious digital literacy, and value-oriented instructional practices. Digital learning contributed to students’ critical thinking, ethical awareness, independent learning, and responsible digital behavior. The study reveals that successful digital transformation in Islamic education depends not only on technological infrastructure but also on teachers’ pedagogical capacity and their ability to internalize Islamic values within digital learning experiences. These findings contribute to the development of Value Based Digital Pedagogy, which integrates technological competence, pedagogical innovation, and Islamic value internalization. Keywords: Character Education, Digital Transformation, Islamic Religious Education, Learning Strategy